Propuesta para la recuperación y reutilización de cromo en lodos galvánicos de Ingecrom Ltda., a nivel laboratorio (2018)
The purpose of this work is to generate a proposal for the recovery and reuse of chromium in galvanic sludge from Ingecrom Ltda., At the laboratory level. In the first instance, the diagnosis of the wastewater treatment plant of the company is carried out, since the sludge that is to be studied is generated, making known the type of water that reaches the plant, the equipment and the process developed in the company for the purification of the waters, and likewise the disposal of the mud and its annual production. According to what was analyzed in the diagnosis, an alternative is proposed by which the chromium contained in the sludge can be recovered, which is why a selection matrix is made with the possible options, evaluating aspects such as: recovery efficiency, availability of equipment costs, time and ease of operation. Selecting in this way and through bibliographic supports the alternative that meets this objective. The experimentation is carried out, carrying out a factorial design 23 of 9 tests with their respective replica, determining with volumetric analysis the chromium existing in the solutions, and obtaining the recovery of hexavalent chromium. Next, the performance of the recovered chromium for the reincorporation of this in the hard chromium process was evaluated, so that respective purification marches were carried out and finally an electrolysis at the laboratory level with the Hull cell. Analyzing qualitatively the coating obtained.